The Black's place in the city image: Afroeuropeans and urban representations in Europe - Taviani, E.; Raposo, O.; Cordeiro, G. Í. (Book of abstracts of the 7th Afroeuropeans Network Conference, 2019)
In this session, we will investigate the visibility/invisibility and the inclusion/exclusion of African populations and people of African descent, within the physical and imaginary borders of Europeans cities with a colonial history. Focusing on both the material and immaterial aspects of the image construction, we will engage in debates concerned with the involvement of African populations and their descendants in current urban representations.